2014
DOI: 10.1021/am507584j
|View full text |Cite
|
Sign up to set email alerts
|

Robust Superhydrophobic Silicon without a Low Surface-Energy Hydrophobic Coating

Abstract: Superhydrophobic surfaces without low surface-energy (hydrophobic) modification such as silanization or (fluoro)polymer coatings are crucial for water-repellent applications that need to survive under harsh UV or IR exposures and mechanical abrasion. In this work, robust low-hysteresis superhydrophobic surfaces are demonstrated using a novel hierarchical silicon structure without a low surface-energy coating. The proposed geometry produces superhydrophobicity out of silicon that is naturally hydrophilic. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 50 publications
4
60
0
Order By: Relevance
“…12,13 Inspired by cicada wings, which are covered with nanopillar-shaped structures that are capable of killing bacteria through physical means rather than by using drug, scientists have discovered a way to reduce bacteria growth. [14][15][16][17][18][19][20][21][22] Specifically, studies have shown that when bacteria land on such nanopillar surfaces with features much smaller than the bacteria themselves, bacterial membranes are ruptured. 14,15 Therefore, an approach which relies on creating nanostructured surface features on the same material to be implanted may represent a novel nonpharmaceutical or non coating approach to reduce orthopedic implant infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Inspired by cicada wings, which are covered with nanopillar-shaped structures that are capable of killing bacteria through physical means rather than by using drug, scientists have discovered a way to reduce bacteria growth. [14][15][16][17][18][19][20][21][22] Specifically, studies have shown that when bacteria land on such nanopillar surfaces with features much smaller than the bacteria themselves, bacterial membranes are ruptured. 14,15 Therefore, an approach which relies on creating nanostructured surface features on the same material to be implanted may represent a novel nonpharmaceutical or non coating approach to reduce orthopedic implant infections.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22] More importantly, the tips of cicada wing nanocolumns were round and capped, which was in contrast to the tips of PEKK which were sharp-edged. Future studies will investigate the influence of the geometry of these PEKK nanoscale surface features and the resultant antibacterial response.…”
mentioning
confidence: 99%
“…Durable superhydrophobic coatings have been reported recently, 26 such as acrylic polyurethane based coating, 27 textured surface obtained by chemical etching, 28,29 surfaces template from innately microstructured hydrogel matrix, 30 block-copolymer-based thin-film patterning, 31 combination of rodlike palygorskite and organosilanes via spray-coating, 32 fluorine-free polysiloxane/multiwalled carbon nanotubes, 33 titanium dioxide materials with special wettability, 34 or various coatings fabricated on fabrics/sponges/cotton. [35][36][37][38][39][40] However, most of the reported surfaces are not durable enough, as they can only resist abrasion against wipes, 28 fine sandpaper (e.g., 800, 1000, 2000 grid), mild droplets/sand impinging, 30,31 or were easily disabled after a short distance (i.e., less than 5 m) of abrasion. 27,29,[41][42][43] Besides, the mechanical stability may be simply due to the fact that the coating thickness is too thick to be worn out completely to expose the substrate surface underneath the superhydrophobic coating.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies that suggest that it is possible to develop superhydrophobic surfaces with only morphological modification (without alteration of the surface chemistry) by providing a low surface energy coating [130][131][132][133]. The superhydrophobic behavior in these cases is achieved by decreasing the liquid-solid contact fraction to a very lower magnitude by morphological modifications.…”
Section: Effectiveness Of Various Coatingsmentioning
confidence: 99%